Biocontrol potential of newly isolated Streptomyces noursei D337-11 from disease suppressive soil and its metabolites against Fusarium oxysporum f. sp. cubense in banana plants - Zhou, Dengbo; He, Xinxin; Chen, Yufeng; Li, Chunting; Wang, Wei; Pan, Zhiqiang; Zhao, Yankun; Wei, Yongzan; Feng, Junting; Zhang, Miaoyi; Qi, Dengfeng; Li, Xiaojuan; et al. (Frontiers in Microbiology, 2025)
Banana Fusarium wilt, caused by Fusarium oxysporum f. sp. cubense, threatens global banana production. Biocontrol using Streptomyces is a promising strategy. Here, we identified Streptomyces noursei D337-11 from disease suppressive banana soils, which exhibited dual functionality in controlling F. oxysporum f. sp. cubense tropical race 4 (Foc TR4), achieving a 65.35% suppression of disease, and promoting plant growth in pot experiments. The extracts from this strain restored the soil microbiota disrupted by Foc TR4, particularly, reviving Saccharimonadales populations. Using integrated untargeted metabolomics (LC-ESIMS/MS) and genomic analysis, we identified five bioactive metabolites, including naringenin, a flavonoid linked to a 100% homologous biosynthetic gene cluster (Region 52.1). Genome-guided differential metabolomics established the genetic basis for flavonoid production. Mechanistic characterization indicated that naringenin exhibits antifungal activity via dual-target inhibition: molecular docking showed strong binding to the trypsin of Foc TR4 (N1RZA7, −6.6 kcal/mol) and nitroalkane oxidase (N1R9V2, −8.4 kcal/mol), which disrupts cellular integrity as evidenced by ultrastructural anomalies. We provide the first evidence of Streptomyces-derived naringenin as a multi-target antifungal agent. Overall, this study provides a theoretical basis for exploring the application of microbial flavonoids in biological control of fungal diseases.